HEPATOPROTECTIVE ACTIVITY OF SEMECARPUS ANACARDIUM FRUIT EXTRACTS AGAINST CARBON TETRACHLORIDE INDUCED HEPATOTOXICITY IN RATS - DR. SAVITA PATIL; DR. KASHINATH GUMMA; DR. MOHAMMED MATEENUDDIN (International Journal of Pharma and Bio Sciences, 2013)
The objective of the present study was to evaluate hepatoprotective activity of fruit extracts of semecarpus anacardium against the damage caused by carbon tetrachloride (1.25mg/kg, p.o.). Aqueous and ethanolic extracts of semecarpus anacardium fruits were administered in the dose of 250 and 500mg/kg/day orally for 7 days. Silymarin (50mg/kg) was used as standard drug. The hepatoprotective effect was assessed by biochemical parameters such as serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), alkaline Phosphatase (ALP), total bilirubin and serum protein. It was concluded that both aqueous and ethanolic extracts showed significant hepatoprotective activity.